Financial Self-Efficacy and Financial Well-Being among Generation Z Workers: The Mediating Role of Financial Stress - Dede Yusuf Maulana; Muhammad Fachmi; Muhammad Muhammad (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
This study aims to examine the effect of financial self-efficacy on financial well being with financial stress as a mediating variable among Generation Z workers in Indonesia. This research employed a quantitative approach using a cross sectional survey design. Data were collected through a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that financial self-efficacy has a negative and significant effect on financial stress and a positive and significant effect on financial well being. Furthermore, financial stress has a negative and significant effect on financial well being. The mediation analysis confirms that financial stress significantly mediates the relationship between financial self efficacy and financial well-being. These findings highlight that psychological capability in managing financial matters plays an important role in improving young workers’ financial well being. This study implies that financial development programs should not only improve financial knowledge but also strengthen financial confidence and strategies for managing financial pressure. Keywords: Financial Self-Efficacy; Financial Stress; Financial Well-Being; Generation Z; PLS-SEM.